Pengendalian Persediaan Label Pakcoy Untuk Menghindari Kekurangan Pengiriman di CV. X Menggunakan Metode Min – Max - Akhsani Nur Amalia, Akhsani Nur Amalia (Teknologi Nusantara, 2023)
The research was conducted so that companies can determine the minimum amount of Label product inventory in the warehouse, so that consumer demand can be met properly. There are three types of labels discussed in this research, namely Pakcoy, Kale and Spinach labels. Non-fulfillment of consumer orders is the basis of this research. If the company cannot meet consumer demand in the expected quantity, there is a risk of losing the opportunity to make a profit. Efforts are needed to control inventory. Determining the amount of inventory is carried out using the min – max method. The results of this research show that the safety stock for Label Pakcoy is 3388 pcs, Kale 1672 pcs and Spinach 1562 pcs. Minimum inventory for Label Pakcoy is 13618 pcs, Kale 8096 pcs and Spinach 5434 pcs. The maximum supply for Label Pakcoy is 20460 pcs, Kale 12848 pcs and Spinach 7744 pcs. Meanwhile, the number of production rounds for Label Pakcoy is 6842 pcs, Kale 4752 pcs and Spinach 2310 pcs.